Values, rewards and job satisfaction: the case of turkish EFL teachers - AYDIN, Fatma ((JELE) Journal Of English Language and Education, 2018)
The present study investigates what aspects of their work are valuable to Turkish EFL teachers working at a state university, and what sorts of rewards they get from their job. The present study also explores how satisfied Turkish EFL teachers working at a state university are with their careers and jobs, and whether gender, age and years of teaching experience play a role in their satisfaction with their careers and jobs. Lastly, the present study analyzes whether teachers’ values or teaching rewards or the interaction between values and rewards predict career and job satisfaction among Turkish EFL teachers working at a state university better. For the accomplishment of the present study, the data were collected by means of the adapted version of a scale instrument on EFL teachers’ values, teaching rewards and career/job satisfaction, created by Kassabgy, Boraie and Schmidt (2001), from a total of 66 English instructors working at Anadolu University School of Foreign Languages (AUSFL). The data were analyzed using a number of statistical procedures, and the findings were interpreted and discussed in accordance with the previous research